Puzzles as A Learning Media In Dance Education for Elementary School Students - Rosarina Giyartini (Universitas Pendidikan Indonesia (UPI), 2020)
This study aims to find the concept of learning dance in elementary schools (SD) using puzzle media. Puzzles were chosen because they are educational toys whose prices are relatively affordable, and their use can be adjusted to the child's level of development. This learning concept is needed especially by teachers who do not have the knowledge of dance education but have to teach dance in elementary schools. To achieve this goal, the material object studied is the essence of learning dance in elementary school and puzzles. The formal object is descriptive correlational, an approach that seeks to describe the phenomenon of the material object being studied and the relationship between these material objects. The results of this study are the concept of using dance puzzles in teaching dance in elementary schools. The sources obtained from this research are the concepts constructed from this research that can be applied to dance learning in elementary schools. One of the implications of the results of this research is that teachers who do not have a scientific basis for dance education can teach dance proportionally in elementary schools.